The Emotive Rational Approaches and Its Effects on Student Behavior - Ahmad Suradi (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2020)
Religious teachers are very important in the moral formation of students, because morals are not enough just to learn, without any strategy to form a moral person. Cultivating the values of good morality have been familiarized in daily life, the habit will be something light. Emotional rational approach is assumed to be able to reduce the number of student delinquency in this problem. Emotional rational approach is an attempt to approach by improving through thinking patterns and eliminating irrational thinking patterns. So this study aims to reveal the effect of emotive rational approaches by religious teachers on student behavior at school. This research method uses quantitative methods, the sample of which is students and teachers of Religion in State Senior High School 4 of Bengkulu City. The results showed that the emotive rational approach affected the behavior of students in State Senior High School 4 of Bengkulu City. Proven by t test calculation of -21,897. While the Sig (2-tailed) value of 0,000 <0.05 so it can be concluded that (Ha) is accepted and (Ho) is rejected, so Ha states that there is an influence of emotive rational approach to student behavior in State Senior High School 4 of Bengkulu City.